1998
DOI: 10.1007/bfb0056270
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted quantitative analysis of deformities of the human spine

Abstract: Abstract. Nowadays, conventional X-ray radiographs are still the images of choice for evaluating spinal deformaties such as scoliosis. However, digital translation reconstruction gives easy access to high quality, digital overview images of the entire spine. This work aims at improving the description of the scoliotic deformity by developing semi-automated tools to assist the extraction of anatomical landmarks (on vertebral bodies and pedicles) and the calculation of deformity quantifying parameters. These too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The fitted 3D curve is then used to perform Lenke and King classification of the type of scoliotic deformities [11,12]. In [7], the user manually fits a 3D Bezier curve with 6 control points to the centerline of the spine in biplanar x-ray images. In addition, the user identifies landmarks on key vertebrae in the images, and the algorithm interpolates the landmarks of other vertebrae based on the fitted 3D curve.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitted 3D curve is then used to perform Lenke and King classification of the type of scoliotic deformities [11,12]. In [7], the user manually fits a 3D Bezier curve with 6 control points to the centerline of the spine in biplanar x-ray images. In addition, the user identifies landmarks on key vertebrae in the images, and the algorithm interpolates the landmarks of other vertebrae based on the fitted 3D curve.…”
Section: Related Workmentioning
confidence: 99%
“…In one extreme, a 3D curve is regarded as a simplified model of the spine, and it is registered to the spine in the x-ray image [5][6][7]. This approach is efficient but its accuracy is not guaranteed due to the simplicity of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Image-based analysis of spinal morphology predominantly involves multiplanar images on which two-dimensional (2-D) segmentation models, e.g., [4] and [5] or 3-D segmentation models, e.g., [6] and [7], are applied. Here, we discuss a number of 3-D models for segmentation of 3-D spinal or vertebral images in terms of boundary model, objective function, model deformation and interaction.…”
Section: Related Workmentioning
confidence: 99%
“…The corresponding standard deviation is (5) The average feature function is investigated for high curvature points on the basis of its local second order properties [23]. These properties are obtained from the infinite set of planes passing through and containing the normal in geometric space at a specific point on the population average surface .…”
Section: ) Surface Representationmentioning
confidence: 99%
“…The fitted curve was used to initialize and rigidly match templates of vertebral body with the image data to obtain vertebral outlines. Verdonck et al [5] manually indicated specific landmarks in the image and founded others using an interpolation technique. The landmarks, together with a manually indicated axis of the spinal column, were used to automatically compute endplates on vertebrae and the global outline of the spine.…”
Section: Introductionmentioning
confidence: 99%